An Analysis of Open Source Software Adoption in a Brazilian Nonprofit University - Prado, Edmir P. Vasques (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2012)
Recently, there has been much effort to foster the adoption of Open Source Software (OSS) in several different countries. Studying the characteristics of new users and the reasons that lead them to adopt OSS can thus help better understand this phenomenon, offering lessons to similar projects. In this context, the present paper addresses the adoption of OSS in a Brazilian university. The paper identified distinct groups of students with different preferences in relation to OSS.